Epimerization of C5 of an N-hydroxypyrrolidine in the synthesis of swainsonine related iminosugars - Qian, B; Kamori, A; Kinami, K; Kato, A; Li, Y; Fleet, G; Yu, C (Royal Society of Chemistry, 2016)
Epimerization of C5 of an N-hydroxypyrrolidine ring by regioselective oxidation to a nitrone followed by diastereoselective reduction provides a newapproachto the synthesis of swainsonine and related compounds. The only protection in the synthesis of the potent mannosidase inhibitor DIM (1, 4-dideoxy-1,4-imino-D-mannitol) was the acetonation of D-mannose.